보건소 비만예방관리 사업 현황 및 요구도 분석 - 박지영(Park, Jiyoung); 임미해(Im, Mihae); 백설향(Baek, Seolhyang); 박종원(Park, Chongwon); 황가희(Hwang, Gahui); 김완수(Kim, Wansoo); 오유미(Oh, Yumi); 조아라(Cho, A Ra); 조지은(Jo, Jieun) (지역사회간호학회지, 2021)
Purpose: The obesity prevention and management program led by public health centers are important in the community. This study aims to identify the current status of obesity prevention and management programs at public health centers and perceptions regarding facilitators and barriers when implementing programs. Methods: This study used a concurrent mixed methods design. A survey was conducted to investigate the current status and infrastructure of the obesity prevention and management program at eighty-three public health centers nationwide. Nine program managers and six local residents with experience in the program were interviewed by using a semi-structured questionnaires. Results: Most of the infrastructure facilities for the program were inadequate, and insufficient budgets and lack of professional staff were identified as barriers. Facilitators included diversification of program delivery methods, operator competence, and visible outcomes and rewards. For the effectiveness of the program, it is vital to have adequate assistants, a sufficient budget, various promotional methods, and connections with various institutions in the community. On this basis, it is acknowledged that the public health center serves as a platform for preventing and managing obesity in the community. Conclusion: It is expected that infrastructure improvements in public health centers and the link with community resources are needed. In addition, there is an urgent need to set standards for obesity prevention and management programs implemented in public health centers to 'resolve regional disparities'.